Revised estimates of personal sector wealth for South Africa - Aron, J; Muellbauer, J (2004)
In common with many emerging market countries, South Africa’s government does not publish balance sheet wealth estimates on a market value basis, as produced in the U.S., U.K., Japan, and elsewhere. Yet without information on the market values of liquid and illiquid personal sector wealth, it is difficult to explain aggregate consumer spending and saving, consumers’ demand for credit, and the broad money holdings of households. Behavioural equations for these variables are key components of central banks macro-econometric models, used in forecasting and policy-making. Understanding the domestic asset value channel of the monetary policy transmission mechanism is especially important for inflation targeting countries. We construct the first coherent set of aggregate, personal sector wealth estimates at market value for South Africa. Our quarterly estimates derive from published data on financial flows, and various other capital market data, often at book value. Our methods rely, where relevant, on accumulating flow of funds data using appropriate benchmarks, and, where necessary, converting book to market values using appropriate asset price indices. Relating asset to income ratios for various asset classes to asset price movements and rates of return, throws light on the changing composition of personal sector wealth. Most striking are the rise in pension wealth - overtaking gross housing assets in the late 1980s; the rise in household debt; and the relative decline of liquid and housing assets, from the early and mid-1980s, respectively.